Comparative Study of the Effects of Clonidine and Tranexamic Acid on Intraoperative Bleeding in Rhinoplasty: A Clinical Trial - Mohammad Bagher Heydari; Maryam Safdari; Behzad Hemmatpoor (JPRAS Open, 2024)
Introduction: The present study was conducted to compare the effects of clonidine and tranexamic acid on the volume of bleeding and quality of the surgical field in terms of bleeding in candidates who underwent rhinoplasty. Methods: In this two-sided clinical trial, candidates eligible for rhinoplasty were randomly assigned to two treatment groups: tranexamic acid and clonidine. The first group received tranexamic acid at a dose of 700 µg/kg of body weight 2 hours before the surgical procedure, whereas the second group received clonidine orally at a dose of 2 mg/kg of body weight, 90 minutes before surgery. Subsequently, the volume of bleeding was calculated based on the amount of blood collected via suction and in blood-soaked gauze, which was previously weighed. Results: Among the 92 patients who underwent rhinoplasty, 82% were women. The mean age and standard deviation (SD) of individuals who underwent rhinoplasty were 29.22 ± 8.50 years. There were no significant differences between the two treatment groups in terms of age, gender, and body mass index. The volume of blood collected via suction during rhinoplasty, categorized into surgery duration <63 minutes and ≤63 minutes, showed a significant difference between the 2 treatment groups. Conclusion: The use of tranexamic acid, compared with clonidine, resulted in lesser intraoperative bleeding and better surgical field quality. Considering the superior effectiveness of tranexamic acid in reducing intraoperative bleeding, it is recommended to use tranexamic acid instead of clonidine in rhinoplasty.